Self-Assembly Mechanism of 1,3:2,4-Di(3,4-dichlorobenzylidene)‑d‑sorbitol and Control of the Supramolecular Chirality - Li, Jingjing; Fan, Kaiqi; Guan, Xidong; Yu, Yingzhe; Song, Jian (Langmuir, 2014)
Dibenzylidene-d-sorbitol (DBS) and its derivatives are known to form gels in organic solvents; however, the mechanism of the gel formation has been a subject of much debate. The present work is undertaken to elucidate the organization mechanism of a DBS derivative, 1,3:2,4-di(3,4-dichlorobenzylidene)-d-sorbitol (DCDBS), by taking into account the solvent effects and comparing the experiment data with theoretical calculation. These molecules form smooth nonhelical fibers with a rest circular dichroism (CD) signal in polar solvents, in contrast to rope-liked left-helical fibers with a strong negative CD signal observed in nonpolar solvents. The molecular complexes thus formed were characterized by means of Fourier transform infrared spectra, ultraviolet–visible spectra, X-ray diffraction patterns, static contact angles, and theoretical calculations. It was proposed that the interactions between the gelator and the solvents could subtly change the stacking of the molecules and hence their self-assembled nanostructures. In nonpolar solvents, the gelator molecules appear as a distorted T-shaped structure with the 6-OH forming intermolecular hydrogen bonds with the acetal oxygens of adjacent gelator molecule. In addition, because of differential stacking interactions on both sides of the 10-member ring skeleton of the gelator, the oligomers may assemble in a helix fashion to minimize the energy, leading to helical fibers. In polar solvents, however, the gelator molecules show a rigid planelike structure and thus stack on top of each other because of strong parallel-displaced π interactions. The balanced driving force on both sides of the 10-member ring skeleton made it difficult for the dimers to bend, thus resulting in nonhelical nanostructure. As expected from the mechanisms proposed here, twisted ribbon fibers with a medium strength CD signal were obtained when solvents of different polarities were mixed. Thus, solvent effects revealed in this work represent an effective means of realizing in situ tuning of nanostructures and control of the expression of chirality at supramolecular levels.